Projeto ótimo de redes coletoras de média tensão em parques eólicos - França Neto, Geraldo Landim de (2023)
Renewable energies are a topic of crucial importance on the world stage. Wind energy occupies an increasing percentage in the energy matrix of countries, and it is no different here in Brazil. The opening of the energy market ends up demanding techniques and tools that help investors in making decisions for medium and long-term investments. One of the main issues related to the construction of wind farms is related to the cost of infrastructure and electrical losses associated with the internal distribution network that connects the wind turbines with each other and with the plant's substation. For this, an integer linear programming model is proposed, which optimizes the definition of the topography of the internal network of the plant and the types of conductors to be used. Variations of the original model are presented with changes in restrictions and inclusion of new variables, such as the cost of line inputs in substations, loss factor and investment analysis considering the net present value. The model simulations consider a wind farm with 52 wind turbines and 2 substations and another with 74 wind turbines and 16 substations. The results obtained show that the proposed changes to the restrictions generate solutions identical to the original model. The inclusion of new variables makes the model closer to reality.